A Comparative Pharmaceutical Evaluation of Amlodipine (5mg) (University of Khartoum Engineering Journal, 2022)
The objective of this study is to evaluate the pharmaceutical properties of three brands of Amlodipine (5mg) for local and international pharmaceutical companies. The main aim is to evaluate whether compliance with the United States Pharmacopeia (USP) is implemented for physical and chemical parameters including: assay, dissolution, hardness, thickness, length and disintegration. A HPLC device was used in the assay test to determine the percentage of the labeled amount of amlodipine (active ingredient) in the portion of tablets or capsules. Results of assay test showed that values for Norvasc, Myodipine and Nordip were 97.83%, 95.31%, and 93.64% respectively, which are within the acceptable range of 90-110% of the labeled amount of amlodipine. UV-VisibleSpectrometer was used in dissolution test to measure the percentage of dissolved amlodipine. Results of dissolution test showed that values for Norvasc, Myodipine and Nordip were 99.795%, 99.415% and 96.61 respectively, which are all within the acceptable range of not less than 75% of the labeled amount of dissolved amlodipine. Tablets andcapsules were subjected to various physical tests which included hardness, thickness, length and disintegration. Results were statistically analyzed as per USP official methods. The study concluded that all brands of Amlodipine Besylate showed satisfactory results for the chemical and physical tests.